Effectiveness of fine-needle aspiration cytology in the diagnosis of lateral cervical nonthyroid tumors. Issue 31 (August 2016) - Iacob, Alina; Zazgyva, Ancuta; Ormenişan, Alina; Mezei, Tibor; Sin, Anca; Tilinca, Mariana
Abstract : Abstract: Given that the clinical and radiological examinations of lateral cervical masses are not always sufficient for deciding on appropriate management, the cytological examination of the material obtained by fine-needle aspiration might be an efficient tool in the preoperative investigation of these lesions. In this prospective cross-sectional study we evaluated the efficacy and diagnostic accuracy of fine-needle aspiration cytology in the assessment of lateral cervical nonthyroid tumors, by comparing its results with those of histopathology. A total of 58 patients with lateral cervical masses were included. Preoperative cytological results were compared with the histopathologic examination of surgical specimens. Both cytology and histology indicated that malignant tumors outnumbered benign lesions (62% vs 38%), with 88.9% of malignancies presenting in patients aged >50 years, but cytology was less effective at differentiating between benign and nontumor lesions. Cytology had 76.5% specificity and 78.1% sensitivity for identifying malignant lateral cervical lesions, and there was a concordance between the two diagnostic tests (McNemar test, P = 0.17, κ = 0.50, P <0.001). Fine-needle aspiration cytology is a simple, quick, and effective procedure that can aid in the preoperative evaluation of lateral cervical masses by differentiating benign tumors and inflammatory processes from malignancies and thus help in determining a subsequent therapeutic strategy.